Student appraisals of collaborative team teaching: A quest for student engagement (Journal of Applied Learning and Teaching, 2023)
Team teaching has been defined many a time in a variety of contexts. However, it is increasingly taking centre stage in addressing the gaps in student learning and is a platform for generating a multiplicity of ideas. We view learning as a product of instructors’ multiple perspectives and teaching experiences. This study aimed to investigate the effectiveness and provide a synthesis of the inherent benefits of team teaching and how it positively contributes to students’ critical thinking skills, learning experiences and engagement. We believe knowledge construction results from a collaborative effort between teachers and students. This supports our choice of constructivist learning theory as an ideal lens for understanding team teaching and its benefits to learners and teachers. Thus, the availability of multiple explanations from the teaching team allows the elaboration of key aspects of the module or course and beyond. Arguably this has a facilitative effect on learning (i.e., allows for knowledge development) through the provision of reflection and timely feedback compared to delayed feedback which potentially hinders learning. The results of this study show that through motivating students, providing clear communication, and involving students in the learning process, deeper engagement is needed. This is facilitated and enhanced by adopting a team-teaching pedagogical approach. This study contributes towards our understanding of students’ learning and that pedagogically, the fundamental efficacy of education requires that learners be served with effective knowledge. It also reminds us that, if not handled well, miscommunication may hamper learning and engagement due to potentially mixed messages.